Allocation strategy of regulated consumption quota ratio of renewable energy based on game theory. (September 2021) - Tang, Difei; Dong, Chenjing; Wu, Xueyan; Qian, Hanhan; Wang, Haichao; Jiang, Hailong; Zhang, Zhi; Chen, Yuge; Deng, Xin; Lin, Zhenzhi; Waseem, Muhammad
Abstract: Fair and reasonable allocation of regulated consumption quota ratio (RCQR) of renewable energy is the foundation and key to guarantee the effective implementation of the mechanism associated with renewable energy consumption in China. Given this background, the allocation strategy of RCQR based on game theory is proposed for guaranteeing the consumption of renewable energy in this paper. In the proposed strategy, the RCQR of renewable energy for the market entities is allocated by determining the reasonable weights based on three proportional allocation methods (i.e., electricity consumption, electricity selling profits, and electricity purchasing cost) and the group satisfaction degree method. Then, game theory is used to coordinate the inconsistency of the four methods of determining weights. Finally, an allocation case of RCQR in Anhui, China is taken as an example for demonstration to verify the effectiveness and practicability of the proposed strategy. The simulation results show that the RCQR can be appropriately allocated by the proposed strategy, and it can be obtained that there is still a certain margin between the obliged consumption under the proposed strategy of each market entity and its maximum acceptable consumption.